2019
DOI: 10.1093/tas/txz115
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: The use of iSperm technology for on-farm measurement of equine sperm motility and concentration

Abstract: The iSperm is a newly released semen analysis tool from Aidmics Biotechnology Co. LTD, which allows an iPad Mini to be transformed into a handheld microscope with objective semen analysis software for equine available through the Apple Store (version 4.5.2). The aim of this study was to compare iSperm values for sperm motility and sperm concentration to current acceptable methods for semen analysis and to determine the agreement with these methods using statistical methods. Two ejaculates from each of five Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
(21 reference statements)
2
9
0
Order By: Relevance
“…However, the authors of this study did not investigate the CV for concentration values generated by the iSperm Equine application. In agreement with our findings, Moraes et al (2019) found that the iSperm Equine application provided accurate TM and PM motility assessment when compared to a CASA system( Moraes et al, 2019 ). In agreement with the existing literature, our result indicate that the iSperm could be a very useful and affordable tool for onsite analysis of canine semen, though we recommend repeated measures for concentration assessment due to the high CV we observed for this parameter.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the authors of this study did not investigate the CV for concentration values generated by the iSperm Equine application. In agreement with our findings, Moraes et al (2019) found that the iSperm Equine application provided accurate TM and PM motility assessment when compared to a CASA system( Moraes et al, 2019 ). In agreement with the existing literature, our result indicate that the iSperm could be a very useful and affordable tool for onsite analysis of canine semen, though we recommend repeated measures for concentration assessment due to the high CV we observed for this parameter.…”
Section: Discussionsupporting
confidence: 90%
“… Moraes et al (2019) concluded that the iSperm Equine application was a valid means for concentration, concentration, total motility, and progressive motility assessment of equine semen. This study found that iSperm Equine assessment of semen concentration did not significantly differ from Nucleocounter or hemocytometer assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability and technical settings of CASA systems have already been extensively investigated and optimized [ 9 , 10 , 11 , 12 ]. The NucleoCounter ® , on the other hand, is a newer device that has rapidly gained in popularity for the assessment of sperm concentration of several species and is now considered as the gold standard in stallions [ 13 , 14 ]. The NucleoCounter ® can discern sperm debris and particles from spermatozoa using a DNA-specific fluorescent dye that stains spermatozoa DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the software iSperm ® , developed by Aidmics Biotechnology (Taipei City, Taiwan), uses the camera of an iPad Mini 4 (Apple Inc., Cupertino, CA, USA) and a heating chamber to capture and analyze multiple videoframes of semen at 37 °C. The iSperm ® software has species-specific settings and its use in stallions [ 14 , 17 ], boars [ 18 ], and stud dogs [ 19 ] has been reported in the literature. This portable tool was found accurate in estimating different semen concentrations when compared with both NucleoCounter ® and hemocytometer in stallions [ 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation